Metaphorical Activation of Personal Resource Experience in the Process of Overcoming Situational Anxiety - Bielikova, Larysa; Plokhikh, Viktor (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2025)
Metaphorical means of reducing situational anxiety in individuals are investigated. The aim of the study is to determine the possibilities of significantly reducing situational anxiety in mature individuals through the appropriate, phased, and personal resource activation-oriented use of metaphorical associative cards (MAC) from the «Cope» set. The study involved 54 mature Ukrainian citizens, including 33 women and 21 men aged 30 to 55 (Me = 40). The following methods were used in the empirical study: the «Coрe» set of metaphorical associative cards (to activate the problematic experience; desired changes in the state and resource experience of the subjects); C. Spielberger's method (to diagnose the level of reactive (situational) and personal anxiety); the Freiburg Personality Questionnaire, Form B (to determine maladaptive mental states). Using the MAC, the following were activated in stages: problematic experience, ideas about the desired state; ideas about obstacles to the desired state; ideas about resources; return to ideas about problematic experience. Results. A significant increase in situational anxiety was found after the stage of activating the problematic experience both in the general group of subjects (Z=-5.968; p< .001), and in subgroups of subjects with high (t=-6.776; p< .001) and moderate (t=-4.497; p< .001) personal and initial situational anxiety. A significant reduction in situational anxiety relative to baseline levels was observed, with a large statistical effect (Cohen's d), as a result of the phased application of MAC in the general group (t=11.259; p< .001; d=1.532) and in subgroups of subjects with high (t=9.890; p < .001; d=1.806) and moderate (t=7.683; p< .001; d=1.568) personality and initial situational anxiety. Conclusions. Appropriate, phased, comprehensive activation through the use of MAC and metaphors of personal experience related to the identification of subjectively significant problematic contradictions, desired mental states, obstacles to desired changes, and personal resources for action through integration processes contribute to a significant reduction in situational anxiety in the subjects.